The perfect pass : what the manager can learn from the football trainer - Weenk, Ed, 1971- (Libros de Cabecera, 2014)
A trainer has to win matches and a manager has to reach results. This metaphor helps the author to explain how to get scores through the big picture of one's business. The objective of the book is to provide some simple and easy to understand reflections that anyone in an organisation can apply in a reasonably short timeframe, allowing them quickly to get a good understanding of the big picture of an organisation and the direction it wants to go. Having established this broader vision, we can then evaluate if it's actually fit for getting there in the best possible way, in terms of internal alignment and coherence of people, infrastructure and processes.